Glymphatic System in the Central Nervous System, a Novel Therapeutic Direction Against Brain Edema After Stroke - Zhou, Xiangyue; Li, Youwei; Lenahan, Cameron; Ou, Yibo; Wang, Minghuan; He, Yue (Frontiers in Aging Neuroscience, 2021)
Stroke is the destruction of brain function and structure, and is caused by either cerebrovascular obstruction or ruptured hemorrhage. It is a disease associated with high mortality and disability worldwide. Brain edema after stroke is an important link affecting nerve function recovery. The formation and recovery of brain edema after stroke are closely related to the glymphatic system. In this review, we will introduce the physiology of the glymphatic system, as well as related mechanisms and therapeutic targets involved in the formation of cerebral edema after stroke, which could provide a new research direction for treating cerebral edema after stroke.